2012
DOI: 10.3109/1354750x.2012.656705
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of preoperative neutrophil-lymphocyte versus platelet-lymphocyte ratio in patients with operable colorectal cancer

Abstract: The objective of this study was to clarify whether the neutrophil-lymphocyte ratio (NLR) and the platelet-lymphocyte ratio (PLR) are significant prognostic markers in patients with resectable colorectal cancer (CRC). A total of 200 patients who underwent curative resection for CRC were enrolled. The NLR and PLR were positively correlated (p < 0.001). Both the NLR and PLR were shown to be good prognostic biomarkers of overall survival (OS) (p=0.002 and p=0.001, respectively). The PLR was an independent prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
334
7
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(366 citation statements)
references
References 30 publications
14
334
7
11
Order By: Relevance
“…The level of platelets is a parameter that indicates severity of inflammation (Klinger and Welkmann 2002;Alexandrakis et al, 2003;Prete et al, 2011;Li et al, 2014). It was reported that survival was shorter in cases with neutrophilia and thrombocytosis (Edwards et al, 2000;Alexandrakis et al, 2003;Kwon et al, 2012). There is no consensus on the idea that neutrophil is associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The level of platelets is a parameter that indicates severity of inflammation (Klinger and Welkmann 2002;Alexandrakis et al, 2003;Prete et al, 2011;Li et al, 2014). It was reported that survival was shorter in cases with neutrophilia and thrombocytosis (Edwards et al, 2000;Alexandrakis et al, 2003;Kwon et al, 2012). There is no consensus on the idea that neutrophil is associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that PLR and NLR are closely related to mortality rate and response to treatment and it was reported that they could be predictive factors (Alexandrakis et al, 2003;Suzuki et al, 2004;Schmidt et al, 2005;Yamanaka et al, 2007;Cedres et al, 2012;Kwon et al, 2012;Wang et al, 2013). Currently, NLR is accepted as a parameter that indicates negatives effects of both increased neutrophil count representing acute inflammation and decreased lymphocyte count representing physiological stress at the same time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have revealed a correlation between clinical outcomes with common solid tumors (colorectal cancer, lung cancer, breast cancer and pancreatic cancer, etc) and systemic inflammatory response, including plasma C-reactive protein (CRP), hypoalbuminemia, and a selective combination of C-reactive protein and albumin termed as Glasgow Prognostic Score (GPS) (Leitch et al, 2007;Hwang et al, 2011;Jiang et al, 2012;Fox et al, 2013;McMillan, 2013). There were also many studies reporting that haematological markers of systemic inflammatory response such as white blood cell count or its components (neutrophil, lymphocyte, neutrophil-lymphocyte ratio (NLR)), platelet, and platelet-lymphocyte ratio (PLR) are also prognostic indicators for cancer clinical outcomes (Yamanaka et al, 2007;Cho et al, 2009;Kishi et al, 2009;Sarraf et al, 2009;Kwon et al, 2012;Dalpiaz et al, 2013;Fox et al, 2013). In addition, other inflammatory factor combinations such as Prognostic Index (PI) and Prognostic Nutritional Index (PNI) have also been linked with prognosis of malignancies (Kasymjanova et al, 2010;Nozoe et al, 2010;Kanda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Wen-Zhuo He 1,2,3 , Chang Jiang 1,2,3 , Chen-Xi Yin 1,2,3 , Gui-Fang Guo 1,2,3 , Ru-Ming Rong 1,2,3 , Hui-Juan Qiu 1,2,3 , Xu-Xian Chen 1,2,3 , Bei Zhang 1,2,3 , Liang-Ping Xia 1,2,3 * lymphocyte ratio (PLR) was also reported as prognostic factor (Kwon et al, 2012;Kemal et al, 2014). γ-glutamyl transpeptidase (GGT), alkaline phosphatase (ALP), lactate dehydrogenase (LDH) which were included in biochemical test, were also showed as prognostic factors (Saif et al, 2005;Koukourakis et al, 2006;Pompella et al, 2006;Franzini et al, 2008;Franzini et al, 2009;Xie et al, 2014).…”
Section: Prognostic Model Built On Blood-based Biomarkers In Patientsmentioning
confidence: 99%